PENGARUH KOMPETENSI, KOMPLEKSITAS TUGAS, SKEPTISISME PROFESIONAL, INDEPENDENSI DAN KECERDASAN EMOSIONAL TERHADAP KUALITAS AUDIT AUDITOR BADAN PEMERIKSA KEUANGAN (BPK) REPUBLIK INDONESIADAN BADAN PENGAWAS KEUANGAN DAN PEMBANGUNAN (BPKP) PERWAKILAN PROVINSI - Cudtia Lizka Abdika; Amries Rusli Tanjung; Enni Savitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to examine the effect of competence, complexity, professional skepticism, independence and emotional intelligence of the quality audit at the Supreme Audit Agency (BPK) of the Republic of Indonesia and the Finance and Development Supervisory Agency (BPK) Representative Riau Province. The population in this study were all auditors working at the Supreme Audit Agency (BPK), amounting to 117 auditors and the Audit and Development Agency (BPK) Representative Riau province, amounting to 58 auditors. The sampling technique using sample selection method ( purposive sampling method). Criteria sample used was Auditors who have worked more than 2 years at the Supreme Audit Agency (BPK) and the Supreme Audit Agency (BPKP) Representative Riau province and number as many as 115 people. The results showed that the variable competence, complexity, professional skepticism significant effect on audit quality on the Supreme Audit Agency (BPK) and the Supreme Audit Agency and development (BPK) Representative Riau Province. While variable independence and emotional intelligence has no effect on audit quality were significant at the Supreme Audit Agency (BPK) and the Supreme Audit Agency and development (BPK) Representative Riau Province.Keywords: Competence , Complexity , Professional Skepticism , Independence , Emotional Intelligence and Quality Audit.